The cassava monitoring survey in Nigeria: final report - Assfaw Wossen, Tesfamicheal; Girma Tessema, G.; Abdoulaye, Tahirou; Rabbi, Ismail Y.; Olanrewaju, A.S.; Bentley, J.; Alene, A.; Feleke, S.; Kulakow, Peter A.; Asumugha, G.N.; Abass, A.; Tokula, M.; et al. (International Institute of Tropical Agriculture, 2017)
The Bill & Melinda Gates Foundation (BMGF) and the CGIAR Research Program on Roots, Tubers and Bananas (RTB) cofunded the Cassava Monitoring Survey (CMS) project with the objective of documenting the extent of adoption of improved cassava varieties with a rigorous sampling and DNA based identification of improved varieties in Nigeria. For examining the determinants of adoption, the project undertook the following four major tasks: (i) Large-scale household (HH) survey (2500 households from the states responsible for 80% of cassava production in Nigeria), (ii) DNAbased varietal identification using single nucleotide polymorphism (SNP), (iii) GPS-assisted area measurement and (iv) gender-differentiated end-user surveys on varietal and trait preferences. This Executive summary presents the main results from each component.